SUMBER DAN MEDIA PENDIDIKAN ISLAM PERSPEKTIF AL-QUR'AN DAN HADITS - Anisa, Hafilda; Adawiyah, Rindang Rabi’ah; Nanda Hanafi, Sal Shakhiba Albira; Basri, Hasan (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2024)
This research examines the importance of sources and media of Islamic education from the perspective of the Qur’an and Hadith. Islamic education covers all aspects of life, with the Qur’an and Hadith as its main sources. This topic was chosen because Islamic education does not only focus on spiritual and moral aspects, but must also be able to integrate modern technology and media in the learning process. In the midst of rapid technological development, the use of appropriate media is key to bridging students with the challenges of the modern world, strengthening religious understanding, and improving the quality of learning outcomes. This research uses the literature research method, collecting data from books, articles, journals, and online sources. The results show that the Qur’an, As-Sunnah and ijtihad are the main sources of Islamic education, while educational media, both traditional and modern, have proven effective in stimulating interest in learning, strengthening memory and improving students’ academic performance. This research also emphasizes the need for continuous innovation in the development of Islamic education media to face the challenges of the digital era, while ensuring that Islamic values remain relevant and applicable in daily life.